Penafsiran Al-Qur'an: Kajian dari Berbagai Demensi - Shihab, Muhammad Quraish (Jurnal Usuluddin, 1997)
The explanatory translation of the Quran has been made in various dimentions till the contemporary moment. The current study attempts to analyse the development by focusing on tafsir bi al-Ma'thur and tafsir bi al-Ra'yi to tafsir tahlili, muqaran and maudu'iy.